The Social Phenomenology of Alfred Schutz and the Development of Special Education in Society - Christian Sunday Agama; Ignatius Nnaemeka Onwuatuegwu (Journal of Public Representative and Society Provision, 2023)
Teaching profession is considered to be a social action that is set in the life-world, where intersubjective relations are demonstrated and must be valued by the teacher in any circumstance in which it acts. In an attempt to equalize educational opportunity for all learners, a deep insight into education of exceptional students is emphatically given due consideration. This study drew attention to the main idea of social phenomenology of Alfred Schutz and how it could be of assistance in providing a full integration of exceptional students in society. It presented the needs of implementing social action to different kinds of exceptionalities in special educational system from the perspective of social phenomenology of Alfred Schutz. By incorporating Schutz’s conceptional theory of social action into special education, this paper recommended that the special education teachers should be more concerned on mutual understanding and accepting the subjects’ psychological state of mind and other problems they encounter academically. They should value and apply the aspects accentuated by this theory within the educational framework.